Treatment of a case of severe insulin resistance as a result of a PIK3R1 mutation with a sodium–glucose cotransporter 2 inhibitor. Issue 5 (25th March 2018) - Hamaguchi, Tetsushi; Hirota, Yushi; Takeuchi, Takehito; Nakagawa, Yasushi; Matsuoka, Atsuko; Matsumoto, Masaaki; Awano, Hiroyuki; Iijima, Kazumoto; Cha, Pei Chieng; Satake, Wataru; Toda, Tatsushi; Ogawa, Wataru
Abstract: A Japanese woman aged in her late 30s with severe insulin resistance and bodily features including a triangular face, prominent forehead, small chin, large and low‐set ears, and ocular depression was investigated. A similar phenotype was not observed in other family members with the exception of her son, suggesting that the condition was caused by a de novo mutation that was transmitted from mother to son. Exome analysis showed the presence in the proband and her son of a c.1945C>T mutation in PIK3R1, a common mutation associated with SHORT (short stature, hyperextensibility of joints and/or inguinal hernia, ocular depression, Rieger anomaly, and teething delay) syndrome. Administration of a sodium–glucose cotransporter 2 inhibitor lowered the proband's hemoglobin A1c level and allowed a reduction in her insulin dose without treatment‐related adverse events including ketoacidosis, exaggerated loss of body mass or hypoglycemia. Sodium–glucose cotransporter 2 inhibitors might thus offer an additional option for the treatment of genetic syndromes of severe insulin resistance. Abstract : We here report the first Japanese case of severe insulin resistance caused by a mutation in the gene encoding the p85α regulatory subunit of phosphatidylinositol 3‐kinase (PIK3R1), a key mediator of insulin signaling. We also describe here the clinical effects of treatment of this case with a sodium‐glucose cotransporter–2 (SGLT‐2) inhibitor.